Resolva a expressão algébrica apresentada:
10- (8x-2) = 5x+2(-4x+1)
Soluções para a tarefa
Respondido por
2
Good evening !!!
![10 - (8x - 2) = 5x + 2( - 4x + 1) \\ \\ 10 - 8x + 8 = 5x - 8x + 2 \\ \\ 10 = 5x \\ \\ 5x = 10 \\ \\ x = 2 10 - (8x - 2) = 5x + 2( - 4x + 1) \\ \\ 10 - 8x + 8 = 5x - 8x + 2 \\ \\ 10 = 5x \\ \\ 5x = 10 \\ \\ x = 2](https://tex.z-dn.net/?f=10+-+%288x+-+2%29+%3D+5x+%2B+2%28+-+4x+%2B+1%29+%5C%5C++%5C%5C+10+-+8x+%2B+8+%3D+5x+-+8x+%2B+2+%5C%5C++%5C%5C+10+%3D+5x+%5C%5C++%5C%5C+5x+%3D+10+%5C%5C++%5C%5C+x+%3D+2)
espero que eu tenha conseguido te ajudar...
espero que eu tenha conseguido te ajudar...
Perguntas interessantes